Estrutura e dinâmica da fauna de rotíferos (Rotifera) em diferentes hatitats de um lago de água preta (Lago Tupé), na Amazônia Central, Brasil. - Rimachi, Elvis Vasquez (Instituto Nacional de Pesquisas da Amazônia - INPA, 2011)
Studies of rotifers in the Amazon basin has been concentrated in the limnetic region, leaving aside important habitats as the littoral zone. The objective of this study was to determine the composition, species richness, diversity and abundance of rotifers, associated with different habitats of Lake Tupe, and its variation along the hydrological cycle. The habitats studied comprised those related to the central region of the lake (limnetic region, background and sediment from the bottom) and those linked to the littoral (Utricularia foliosa’s stands, leaf litter and submerged igapó forest). The sampling period was in April, June, September, October and November/08 and February/09, obtaining qualitative and quantitative data. We recorded a total of 169 taxa, especially the family Lecanidae with the highest number of taxa. The most frequent taxa in all environments of Tupé lake were Brachionus zanhniseri, B. zahniseri reductus, Keratella cochlearis, Polyarthra vulgaris, sp Ptygura, Trichocerca similis and Bdelloidea. The highest species richness were observed in the forest igapó (119 taxa) in Utricularia’s banks (109 taxa) and submerged litter (94 taxa). The water intake of the Rio Negro was not a determinant to the species richness in the limnetic region at the bottom of the lake, but it was for the generation of new habitats in the region of the margin. The abundances between sampling periods had significant differences (ANOVA, p>0.05) while no difference was detectedt between habitats (limnetic region, background and igapó forest). The calculated diversity index was high, placing the lake Tupé between the environments of greater diversity in the Amazon basin. A canonical correspondence analysis (CCA) did not show clearly that the environmental factors measures in this work influenced the abundance of rotifers at the bottom of lake and at the igapó forest, and only observed in the limnetic a significant correlation (Monte Carlo test, p=0.04) between the abundance of Brachionus zahniseri with depth and transparency.
Keywords: Rotifera; Utricularia foliosa; Amazônia Central